Transcriptomic alterations in malignant pleural mesothelioma cells in response to long-term treatment with bullfrog sialic acid-binding lectin - Tatsuta, Takeo (Mol Med Rep, 2021)
Malignant pleural mesothelioma (MPM) is a universally lethal type of cancer that is increasing in incidence worldwide; therefore, the development of new drugs for MPM is an urgent task. Bullfrog sialic acid-binding lectin (cSBL) is a multifunctional protein that has carbohydrate-binding and ribonuclease activities. cSBL exerts marked antitumor activity against numerous types of cancer cells, with low toxicity to normal cells. Although in vitro and in vivo studies revealed that cSBL was effective against MPM, the mechanism by which cSBL exerts antitumor effects is not fully understood. To further understand the mechanism of action of cSBL, the present study aimed to identify the key molecules whose expression was affected by cSBL. The present study established cSBL-resistant MPM cells. Microarray analyses revealed that there were significant pleiotropic changes in the expression profiles of several genes, including multiple genes involved in metabolic pathways in cSBL-resistant cells. Furthermore, the expression of some members of the aldo-keto reductase family was revealed to be markedly downregulated in these cells. Among these, it was particularly interesting that cSBL action reduced the level of AKR1B10, which has been reported as a biomarker candidate for MPM prognosis. These findings revealed novel aspects of the effect of cSBL, which may contribute to the development of new therapeutic strategies for MPM.